Bioinformatics analysis of mitochondrial metabolism-related genes demonstrates their importance in renal cell carcinoma - Mohsen Ahmadi; Maryam Motallebinezhad; Pegah Mousavi; Amir Hossein Miladipour; Shamim Fooladgar; Soudeh Ghafouri-Fard; Seyed Amirhossein Fazeli (Discover Oncology)
Abstract Purpose Clear cell renal cell carcinoma (ccRCC) is resistant to radiotherapy and chemotherapy. Thus, it is necessary to find new diagnostic markers and therapeutic targets to increase the overall outcomes of ccRCC. Recent studies have shown that therapeutic methods that interfere with the energy transfer system can also positively affect the treatment process. Methods The present study is focused on finding markers associated with mitochondrial metabolic pathways that affect the outcome of ccRCC. For this purpose, we investigated various aspects of the relationship between mitochondrial metabolism and ccRCC based on analysis of gene network connections and differentially expressed genes, through assessment of protein–protein interaction, mutations, and promoter methylation on the related genes. We also investigated gene interaction with miRNAs and immune infiltration analysis. Results Through these steps, we provided a list of possible diagnostic markers and therapeutic targets for ccRCC. Conclusion The current study further proved the importance of mitochondrial metabolic pathways in the pathogenesis of ccRCC and provided a list of possible diagnostic markers and therapeutic targets from these pathways that can be used in ccRCC.